Issues of taxation of small and medium business entities during the development of their activities during the covid-19 crisis (Eurasian Research Bulletin, 2023)
In the article, the Covid 19 pandemic showed its unprecedented negative impact on the economy, social and political life of the countries of the world, in particular, it is noted that the industrial and business sector of the world economy, especially small business and private entrepreneurship, is the most affected sector. Despite this, during the pandemic, a number of indulgences and benefits were provided in order to save small businesses and private entrepreneurship entities in our country as much as possible, to bring them out of the crisis period with minimal damage. This article continues the main directions of infrastructures to support the development of small businesses and private entrepreneurship during the pandemic and the work carried out over the еars. In this regard, conclusions and proposals have been developed on the taxation of enterprises based on the positive results of their activities.